WORKSHOP PENGGUNAAN MIKROKONTROLER BAGI GURU DI SMK NEGERI 1 KLATEN - Suradi, Agustinus; Yusuf, Mahmud; Wuryandari, Aryati (LPPM Universitas Widya Dharma Klaten, 2023)
Vocational High School is one of the educational institutions that is responsible for creating human resources who have the ability, skills and expertise, so that graduates are ready to enter the world of work. SMK Negeri 1 Klaten, Central Java, especially lecturers in the department of computer and telecommunications network engineering, has the hope that it is necessary to explore the material and develop learning in the practical use of the Arduino microcontroller. The purpose of this activity is to implement the use of microcontrollers on devices that require automatic controllers such as machine controllers, IoT relay control, home security systems, and also other electronic equipment. The PKM activity method is carried out in stages: observation & requirements analysis, communication & dialogue, workshop, and evaluation. As a result of this activity, the workshop participants participated actively and looked enthusiastic in the activity by diligently asking questions. In the evaluation of the workshop, the results of the practicum were obtained: 75% of the participants succeeded well, and 25% of the participants with good enough results and were able to carry out the practicum independently.